Twenty years trends and socio-demographic characteristics of HIV prevalence in women giving birth in Catalonia (Spain) - Dolors Carnicer-Pont; Alexandra Montoliu; José Luis Marín; Jesús Almeda; Victoria González; Rafael Muñoz; Carmen Martínez; Mireia Jané; Jordi Casabona (Gaceta Sanitaria, 2015)
Background: Studies of the prevalence of HIV in sentinel populations are one of the key strategies to monitor the HIV epidemic. We describe HIV prevalence trends and identify differences across time in the sociodemographic characteristics of HIV-infected women giving birth in Catalonia. Methods: We used dried blood specimens, residual to newborn screening, which have been collected in Catalonia every 2 months since 1994. The total number of samples obtained until 2009 and in 2013 represented half of yearly newborns. From 2010 to 2012, the total number of samples obtained represented a quarter of yearly newborns. We studied the prevalence by year and place of current residence (Barcelona-city, cities > 200,000 inhabitants and cities ≤ 200,000 inhabitants) and by the mother's birth country. A total of 624,912 infants were tested for HIV antibodies from January 1994 to December 2013. Results: HIV prevalence trends among women giving birth in Catalonia decreased until 2007. Thereafter, there was a change to a steady trend until 2013. However, among foreign women giving birth and living in cities ≤ 200,000 inhabitants, the prevalence of HIV increased from 2007 to 2013. Conclusion: To ensure early identification and treatment of HIV-infected mothers, it is essential to maintain HIV surveillance programs and pre- and post-natal screening programs, both in Barcelona and in cities with 200,000 inhabitants or less, especially in immigrant women.